An integrated approach to microalgae biomass generation and processing - Pearce, Matthew William (Cranfield University, 2016)
Liquid combustible fossil fuel empowers global society, yet is a non-renewable entity with time-constrained limits to supply. Advanced generation biofuel derived from microalgae could feasibly yield more than conventional biofuel crops, utilise non-agricultural land or the sea and remediate atmospheric carbon dioxide and anthropogenic waste. However, technical and economical limits have so far prevented the successful implementation of microalgae biofuels. This thesis exemplifies how apparently disconnected technologies are able to become united in their provision for the growth and processing of microalgae. In so doing, it employs unique experimental methodology which unites inter- disciplinary themes with the proposition to cultivate and process microalgae biomass in a manner which has never been done before. The novelty of this endeavour presents a unique set of challenges, reasoning and results with implications for future creative research and investigation. The philosophical approach to conception and achievement of the laboratory work intercedes with entirely new methodology. Selected examples of such methodology follow. In chapter 3, a newly developed bio-composite gel disk was processed aligning a new design of apparatus for a geotextile puncture resistance test. In chapter 3, a novel formulation for harvesting microalgae is described. In chapter 5, a modified methodology of the preceding chapter is used to investigate seawater ion remediation via ionic and density phase separation. Chapter 6 integrates waste components from 5 different industries, namely dairy farming, anaerobic digestion, brewing, steel slag aggregates and coal power combustion with no previously known unification of such technologies in scientific literature. Chapter 7 assesses the lipid quality of biomass harvested by the novel formulation of chapter 3, before and after exposure to hydrothermal liquefaction. Chapter 8 extrapolates findings from the thesis to define an economic appraisal and suggest a cost saving process.